Opportunistic Use of Client Repeaters to Improve Performance of WLANs - Bahl, Victor; Chandra, Ranveer; Lee, Patrick; Misra, Vishal; Padhye, Jitu; Rubenstein, Dan; Yu, Yan (2008)
Currently deployed IEEE 802.11WLANs (Wi-Fi networks) share access point (AP) bandwidth on a per-packet basis. However, the various stations communicating with the AP often have different signal qualities, resulting in different transmission rates. This induces a phenomenon known as the rate anomaly problem, in which stations with lower signal quality transmit at lower rates and consume a significant majority of airtime, thereby dramatically reducing the throughput of stations transmitting at high rates. We propose a practical, deployable system, called Soft- Repeater, in which stations cooperatively address the rate anomaly problem. Specifically, higher-rate Wi-Fi stations opportunistically transform themselves into repeaters for stations with low data-rates when transmitting to/from the AP. The key challenge is to determine when it is beneficial to enable the repeater functionality. In this paper, we propose an initiation protocol that ensures that repeater functionality is enabled only when appropriate. Also, our system can run directly on top of today’s 802.11 infrastructure networks. We evaluate our system using simulation and testbed implementation, and find that SoftRepeater can improve cumulative throughput by up to 200%.